Acceptance of Solar Technology by Farmers in Vietnam - Nguyen, Quoc Nghi; Mai, Van Nam; Hoang, Thi Hong Loc (International Journal of Energy Economics and Policy, 2023)
This study aims to explain the acceptance of solar technology by farmers in Vietnam. The study combines the Theory of Planned Behavior (TPB) and the Technology Acceptance Model (TAM), supplemented with additional factors (concern for the environment, trust in technology, and supporting policies) to address the research objectives. The study uses quota sampling to collect data from 248 farmers in 4 provinces (Hau Giang, Dong Thap, Bac Lieu, and Kien Giang) in the Mekong Delta region, Vietnam. By applying the Structural Equation Modeling (SEM) approach, the research results demonstrated the positive influences of various factors on the intention to use solar technology among farmers, including perceived ease of use, perceived usefulness, subjective norms, attitude, perceived behavioral control, concern for the environment, trust in technology, and supporting policies. Among these factors, trust in technology was found to have the most impact on the intention to use solar technology among farmers in Vietnam.